Digital Ethics - Jessica Reyman, Erika M. Sparby (Rhetoric and Responsibility in Online Aggressio, 2019)
Digital Ethics delves into the shifting legal and ethical landscape in digital spaces and explores productive approaches for theorizing, understanding, and navigating through difficult ethical issues online.